Investigation of Psychological Factors Based on Health Belief Model and Health Literacy on Adult Self-Medication in Bushehr Province - Homamodin Javadzade; Marzieh Mahmoodi; Gholamreza Sharifirad; Mohadese Fakhraee; Mahnoush Reisi (Mashhad University of Medical Sciences, 2020)
Background and Objective: Self-medication is a high prevalent behavioral choice that may lead to serious consequences. it is necessary to identify the factors that influence and modify this behavior. In this regard, this study aimed to investigate the role of psychological factors and health literacy on self-medication behavior in adults in Bushehr province. Materials and Methods: This is a cross-sectional descriptive-analytic study that was conducted on 1013 persons referred to Bushehr comprehensive health centers. The subjects were selected through convenience sampling and completed demographic, knowledge, psychological constructs of health belief model, health literacy, and self-medication questionnaires. Data were analyzed using independent t-test, chi-square and logistic regression models in SPSS software version 22. Results: Based on the results, occupational status, insurance coverage, knowledge, perceived susceptibility, perceived severity and critical health literacy were predictors of self-medication behavior. According to the results, laborers and retirees were less likely to self-medicate than the unemployed as well as those who were not covered by insurance in comparison to those who were covered by the insurance services. Other results also showed that subjects with higher knowledge and perceived susceptibility had a 1.34- and 1.77-times higher odds of self-medication, respectively. Individuals with higher perceived severity and higher critical health literacy were less likely to practice self-medication. Conclusion: Improving health insurance coverage and attention to occupation and knowledge, as well as modifying perceived susceptibility and severity beliefs, beside the considering and promoting critical health literacy can be effective in modifying self-medication behavior in individuals.